91.9k views
4 votes
Can anyone help with this please

Can anyone help with this please-example-1
User Huantao
by
5.9k points

1 Answer

5 votes

For this case we have a function of the form
y = f (x), where:


f (x) = \frac {5 + x} {6 + 3x}

We must evaluate the function at
x = a-1

So:


g (a-1) = \frac {5+ (a-1)} {6 + 3 (a-1)}\\g (a-1) = \frac {5 + a-1} {6 + 3a-3}\\g (a-1) = \frac {4 + a} {3 + 3a}

Thus, the value of the function is:


\frac {4 + a} {3 + 3a}

Answer:


g (a-1) = \frac {4 + a} {3 + 3a}

User Christopher Smit
by
6.8k points